(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
In today’s fast-paced e-commerce landscape, marketing automation is no longer just a tool for automating repetitive marketing tasks—it has evolved into a powerful system that drives operational efficiency across entire workflows. The integration of marketing automation with operations, logistics, inventory management, and customer service has enabled businesses to scale, optimize performance, and provide personalized experiences at an unprecedented rate. Marketing automation platforms such as HubSpot, Marketo, and Salesforce have revolutionized the way e-commerce companies interact with their customers while streamlining internal processes.